THE ROLE OF FACTORS AFFECTING THE FORMATION OF CHRONIC HEART FAILURE WITH PRESERVED EJECTION FRACTION - M. V. Kurkina; A. G. Avtandilov; I. A. Krutovcev (Столичная издательская компания, 2017)
Aim. To study the combination and contribution of risk factors (age, hypertension (HT), obesity, diabetes mellitus, chronic kidney disease (CKD), length of illness) leading to the formation of chronic heart failure (CHF) with preserved ejection fraction (EF).Material and methods. The study included 100 hypertensive patients (aged 40 to 80 years) with concomitant obesity or diabetes or CKD. Patients were divided into 4 groups depending on the presence of one major and/or several concomitant diseases. Echocardiography, assessment of large arterial vessels stiffness indices (SI m/s, CAVI m/s), and determination of small muscle arteries tonus (RI%) were performed in all patients.Results. Remodeling of the left ventricle (LV) and left atrial (LA) was observed in all patients with comorbid status, as well as reduction in diastolic function. The LV myocardial mass index in the first group was 117.2±31.4 g/m2, in the second one - 125.9±27.4 g/m2, in the third group - 121.5±15.6 g/m2 and in the fourth one - 126.1±11.5 g/m2. A significant increase in the LA volume index was founded in the first group  - 33.4±3.9 ml/m2, in the second one - 39.6±9.1 ml/m2, in the third group - 38.1±5.2 ml/m2 and in the fourth one - 39.8±6.6 ml/m2 (р<0.05). The parameters reflecting the rigidity of large arterial vessels (SI m/s, CAVI m/s) also exceeded the threshold values in each group; significant differences SI were between the first and fourth, second  and fourth groups  (р<0.05), CAVI between the first and third groups  (р<0.05). A significant correlation was found between CAVI and age (r=0.63), which indicated an increase in arterial stiffness with age.Conclusions. In the formation of CHF with preserved EF, additional factors enhance the changes associated with LV remodeling and LA overload. These changes occur with a progressive decrease in LV diastolic function and increase in myocardial stiffness. HT and obesity are the main contributors to the development of CHF with preserved EF. Remodeling of the LV, LA and vascular system in CHF with preserved EF develop simultaneously.